Ratio-Based Financial Performance Analysis of PT. Mustika Ratu, Tbk - Ella Silvana Ginting (Enrichment : Journal of Management, 2021)
Financial ratio analysis is a company performance analysis instrument that describes various financial relationships and indicators, intended to show changes in financial conditions or operating performance in the past and help describe the trend of such changes, to then show the risks and opportunities inherent in the company. . The purpose of this study is to analyze the financial performance based on the ratio of PT. Mustika Ratu, Tbk in the period 2012 to 2017. The data analysis technique used in this study is a descriptive analysis with a qualitative approach. The result obtained is the financial performance of PT. Mustika Ratu, Tbk from 2012-2017 experienced fluctuations every year. As for the effect of the fluctuation of PT's financial ratios, Mustika Ratu, Tbk from 2012-2017 was influenced by several external and internal factors of the company itself, so new measures are needed to improve the company's performance carried out by PT. Mustika Ratu, Tbk to be able to answer the needs of the market and close to the market itself.